Aktualisasi Manajemen POAC Pondok Pesantren Bait Et-Tauhied dalam Membentuk Karakter Santri yang Religius di Era Globalisasi - Diah Robiatul Adawiah; Machdum Bahtiar; Aspandi (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to identify, analyze and provide updates to the actualization of POAC management of the Bait Et-Tauhied Islamic boarding school in the context of forming the character of religious students in the era of globalization. The research was conducted using field research methods with a qualitative approach. Data collection is done by observation, interviews, and documentation. Presentation, reduction, and verification are some of the data analysis methods that can be used. The results of the study show several ways POAC management is used in the Bait Et-Tauhied Islamic boarding school to shape the character of religious students in the modern era. Some examples are planning management that designs the vision, mission, and goals of Islamic boarding school education through character education programs, organizing management divides the main tasks and functions for each field implemented, and actuating management that uses habituation methods with activities involving religious activities.